Wastewater Engineering Issues, Trends, and Solutions - Gupta, Ashok Kumar; Uddameri, Venkatesh; Majumder, Abhradeep; Nimbhorkar, Shripad K. (Shripad Khanderao) (CRC Press, 2024)
Wastewater Engineering: Issues, Trends, and Solutions explains current treatment scenarios of wastewater in different countries across the globe, the characteristics of wastewater, and rules and regulations associated with the treatment and disposal/reuse of wastewater. It covers the design and theory involving laying of sewerage network and different conventional and advanced treatment technologies employed to treat domestic wastewater. It overviews different types of emerging contaminants and their properties, ecological impacts, detection/quantification, treatment technologies, and circular economy. Features: Gives out overview of current wastewater treatment scenarios across the world. Provides insights into emerging contaminants sources, procedure to sample, available methods for analyses, and possible treatments. Reviews existing rules and regulations on wastewater engineering and standards for wastewater disposal or reuse. Includes how to use wastewater as a resource in the context of circular economy. Describes fundamentals of wastewater conveyance, and treatment. The book is aimed at graduate students and researchers in wastewater treatment, water, and environmental engineering.